Diabetic mitochondria are resistant to palmitoyl CoA inhibition of respiration, which is detrimental during ischemia. Issue 8 (28th July 2021) - Kerr, M.; Dennis, K. M. J. H.; Carr, C. A.; Fuller, W.; Berridge, G.; Rohling, S.; Aitken, C. L.; Lopez, C.; Fischer, R.; Miller, J. J.; Clarke, K.; Tyler, D. J.; et al.
Abstract: The bioactive lipid intermediate palmitoyl CoA (PCoA) can inhibit mitochondrial ADP/ATP transport, though the physiological relevance of this regulation remains unclear. We questioned whether myocardial ischemia provides a pathological setting in which PCoA regulation of ADP/ATP transport would be beneficial, and secondly, whether the chronically elevated lipid content within the diabetic heart could make mitochondria less sensitive to the effects of PCoA. PCoA acutely decreased ADP‐stimulated state 3 respiration and increased the apparent K m for ADP twofold. The half maximal inhibitory concentration (IC50 ) of PCoA in control mitochondria was 22 µM. This inhibitory effect of PCoA on respiration was blunted in diabetic mitochondria, with no significant difference in the K m for ADP in the presence of PCoA, and an increase in the IC50 to 32 µM PCoA. The competitive inhibition by PCoA was localised to the phosphorylation apparatus, particularly the ADP/ATP carrier (AAC). During ischemia, the AAC imports ATP into the mitochondria, where it is hydrolysed by reversal of the ATP synthase, regenerating the membrane potential. Addition of PCoA dose‐dependently prevented this wasteful ATP hydrolysis for membrane repolarisation during ischemia, however, this beneficial effect was blunted in diabetic mitochondria. Finally, using 31 P‐magnetic resonance spectroscopy we demonstrated that diabetic hearts lose ATP more rapidly during ischemia, with a threefold higher ATP decay rate compared with control hearts. In conclusion, PCoA plays a role in protecting mitochondrial energetics during ischemia, by preventing wasteful ATP hydrolysis. However, this beneficial effect is blunted in diabetes, contributing to the impaired energy metabolism seen during myocardial ischemia in the diabetic heart.